Culinary Tourism at Jakarta Fair, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to explore and describe the dynamics of culinary tourism in the implementation of the 498th Jakarta Fair in 2025 at JIExpo Kemayoran, Central Jakarta. The main focus of the research is to understand the role of culinary tourism as a space for cultural interaction, creative economy promotion, and social visitor experiences in the annual event. A qualitative approach is used with a descriptive method, through participatory observation techniques, in-depth interviews with culinary business actors, visitors, and organizers, and written documentation. The results of the study show that culinary is one of the main attractions of Jakarta Fair, presenting more than 200 types of food from various regions in Indonesia. Business actors, mostly from the MSME sector, use this event to promote products, build branding, and expand market networks. Visitors consider culinary tourism at Jakarta Fair as a pleasant cultural experience, despite facing obstacles such as long queues and high prices. In conclusion, culinary tourism at Jakarta Fair plays a strategic role in strengthening local cultural and economic identity. It is recommended that organizers improve supporting facilities and provide intensive training to MSME actors so that the quality and positive impact of culinary tourism at Jakarta Fair are increasingly optimal.